Portrait of tourist in Nur-Sultan and strategies for attracting target groups of tourists - Abilkhay, Zh.; Mubarak, D.; Tussupova, Sh. (Submitted in partial fulfillment of the requirements for the degree of Bachelor of Service Management In Tourism M.S. Narikbayev KAZGUU University, 2021)
The purpose of this work is to identify the portrait of a tourist in the city of Nur-Sultan, as well as to create strategies for attracting target groups of tourists. This work will be carried out using a qualitative research method, through the collection and analysis of official statistical data. The study consists of three parts, the first part includes theory, statistics, and its importance. In the second part of the study, the portrait of a tourist of the city of Nur-sultan will be analyzed, and in the third part, strategies for attracting target groups of tourists will be described, as well as further recommendations. The result of this study will be two ready-made portraits of tourists: domestic and foreign. Strategies to attract tourists and recommendations with further consequences will also be developed.
Keywords: the portrait of a tourist in the city of Nur-Sultan